Correlation between structural determinants and universal health coverage in 2010 and 2019: An analysis of the global burden of disease study. - Orlando Luiz do Amaral Junior; Maria Laura Braccini Fagundes; Fernando Neves Hugo; Nicholas J Kassebaum; Jessye Melgarejo do Amaral Giordani (PLOS Global Public Health)
Objective To assess the correlation between structural determinants - governance, macroeconomic policies, culture/societal values, and public and social policies - and the Universal Health Coverage (UHC) Effective Coverage Index in 2010 and 2019, in 204 countries and territories. Methods This ecological study analyzed UHC effective coverage in 204 countries and territories using estimates from the Global Burden of Disease (GBD) 2019 study. Structural determinants were examined across five dimensions. Spearman's correlation was used to examine the correlations. Results UHC showed a positive correlation with structural determinants in both years. In 2010, moderate correlations were observed for governance (ρ = 0.61), GDP (ρ = 0.69), SDI (ρ = 0.62), and government expenditure (ρ = 0.58). In 2019, governance (ρ = 0.56), GDP (ρ = 0.71), SDI (ρ = 0.66), and government expenditure (ρ = 0.48) remained significantly correlated with UHC. GDP and SDI consistently showed the strongest correlations in both periods. Conclusion Countries with more favorable structural conditions had greater UHC, emphasizing the influence of governance and socioeconomic context on health systems performance. Persistent disparities highlight the need for policies targeting social and economic inequalities to achieve universal health coverage globally.